Effect of an Educational Intervention Based on Empowerment Model on Awareness, Attitudes, Self-esteem and Self-efficacy of Men in Preventing Prostate Cancer - mohsen hassanpour; ali delshad; ali alemi (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Prostate cancer is a common cancer among men and is considered to be the second cause of death among men after lung cancer. This study was conducted to determine the effect of an educational intervention based on empowerment model on awareness, attitudes, self-esteem and self-efficacy in men aged 35 to 55 years in preventing prostate cancer. Materials and Methods: This randomized clinical trial was conducted in Gonabad in 2013. Sixty men aged 35 to 55 years old were randomly allocated into intervention (n=30) and control (n=30) groups. The intervention group received an education based on individual empowerment model. Data were collected using a valid and reliable questionnaire before and two months after the intervention. By the SPSS-20, we analyzed the collected data using the T- test, Chi-squared test and Fisherchr('39')s exact test. Results: There were no significant differences between the intervention and control groups in terms of all the study variables at baseline (p>0.05). After the intervention, significant differences were shown between the groups regarding awareness (p=0.007), attitude (p=0.041), self-steam (p=0.049) and self-efficacy (p=0.034). Conclusion: Implementing educational intervention in men based on empowerment model would be effective on awareness, attitudes, self-esteem and self-efficacy in preventing prostate cancer.